Clinicians’ attitudes toward patient safety: A sequential explanatory mixed methods study in Saudi Armed Forces hospitals (eastern region) - Alzahrani, Ahmed Saad (Curtin University, 2015)
This sequential explanatory study explores physicians and nurses’ attitudes toward patient safety in the Saudi Armed Forces Hospitals in the eastern region. The study shows that physicians and nurses have discrepant attitudes toward patient safety. Several factors were found to influence their attitudes, including workforce characteristics, management practices, professional culture, patient safety practices and work environment. The study concludes with recommendations for improving patient safety in the study sites and for future studies.